Inclusive education, special education and meaning: Necessary reflections in the light of historical-cultural psychology - Melo , Lana Cristina Barbosa de; Santos , Silvina Faria dos (Seven Editora, 2023)
The pedagogical proposal of the Degree in Physical Education at the Instituto Federal de Roraima -IFRR has as its articulating axis the Special Education teaching modality, in which all curricular components are focused on the knowledge and practices of this modality. In the light of the theoretical framework of Historical-Cultural Psychology of Historical-Critical Pedagogy and supported by Dialectical Historical Materialism, the objective of this study was to verify whether the social meanings produced by academics, in relation to the concepts of Inclusive Education and Special Education, enable understanding of the reality in its complexity overcoming everyday concepts. As a data collection instrument, a questionnaire with open questions was used. The analysis was based on the theoretical framework presented by Leontiev in the discussions concerning the Activity Theory and the connections between social meaning and personal meaning. In summary, the results showed the absence of meanings around what the Special Education and Inclusive Education legislation says that make it possible to interpret what produces the process of exclusion and the maintenance of the complex and contradictory relationship between equality and difference, reflecting the context in which the initial training of teachers in capitalist society is inserted. DOI:https://doi.org/10.56238/alookdevelopv1-195